Spatial Analysis of the Islands of Kaveri: Exploring landscape themes using placemaking indicators - Balaji Venkatachary; Safiya MD; Shruti Mutalikdesai (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Every river's islands allow a variety of uses, assigned to them by the primary stakeholders over centuries of habitation. Identification of these islands based on thematic classification would aid in the decision-making process. Kaveri is a significant river from the south of India, also one of the seven holy rivers. Besides creating a host of unique landscapes, several of its islands are inhabited and also culturally significant. This paper will document and study islands of river Kaveri using parameters such as land use, demography, heritage components and narratives from popular media. Some of these islands are known for their exceptional cultural and natural significance. GIS will be used to map and analyze these islands and its attributes. Thematic classification will be arrived at using indicators of placemaking. This paper will set a precedent to look at river islands and provide a tool kit to classify island landscapes.